Mulheres na questão agrária: um estudo sobre o coletivo "Raízes da Terra" do Acampamento Quilombo Campo Grande, Campo doMeio-MG - Xavier, Gabriela Taíse Poiati (2022)
The way women and men experience spaces is differentiated by class and race, and also by the gender factor, which makes it necessary to geographically understand such spaces. Although there is an increase in geographic studies in the gender approach, these are still scarce in agrarian geography, which makes it necessary to expand such studies. Due to the social and sexual division of work anchored in patriarchy and intensified by capitalism, women are distanced from social, economic and political spaces. In the countryside, this factor is aggravated, since in addition to fighting for insertion in spaces, peasant women also fight for access and permanence in the territories. Allied with their class in socio-territorial movements, such as the MST, peasant women remain in constant disputes and conflicts over spaces and territories. At the Quilombo Campo Grande encampment, in Campo do Meio-MG, through the methodology of militant research that values ​​praxis and social action, 8 semi-structured interviews and several fieldworks were applied that demonstrated that peasant women are in struggle on a local scale, nationally and internationally, thinking about strategies, actions and conquering these spaces that have been denied for so long. The Coletivo de Mulheres Raízes da Terra, created in 2011, demonstrates the territorialization of the struggle of peasant women in the camp. From agroecology and popular peasant feminism, they fight not only for agrarian reform, but also for the social, economic and political emancipation of peasant women, composing what critical agrarian studies understand as “agrarian issues” since the struggle becomes not only for a piece of ground, but for a new anti-patriarchal, anti-racist and anti-capitalist society.